Study of deformation texture in an AZ31 magnesium alloy rolled at wide range of rolling speed and reductions. Issue 1 (April 2015) - Sanjari, M; Tamimi, S; Su, J; Kabir, A S; Hara, K; Utsunomiya, H; Petrov, R; Yue, S; Kestens, L
Abstract: The plasticity of Mg is restricted at low temperatures because: (a) only a small number of deformation mechanisms can be activated, and (b) a preferred crystallographic orientation (texture) develops in wrought alloys, especially in flat-rolled sheets. This causes problems in thin sheet processing as well as component manufacturing from the sheet. In this study, different rolling speeds from 15 to 1000 m/min were employed to warm-roll AZ31B magnesium alloy to different reductions. The results show that AZ31B sheets rolled at 15 m/min and 100 °C has fractured for reductions of more than 30% per pass. However, by increasing the rolling speed to 1000 m/min the rollability was improved significantly and the material can be rolled to reductions of more than 70% per pass. The results show that with increasing strain rate at 100°C, the splitting of basal poles was observed, indicating the activation of more contraction twins and secondary twins.